Investigating language anxiety among Malaysian secondary school students current situation, sources and strategies - Nurul'ain, Kamaruddin (2009)
The construct of anxiety is believed to have a significant influence on L2 learning. The present study investigated anxiety from 5 perspectives: the relationship between anxiety and achievement, anxiety and gender, sources of anxiety, manifestation of anxiety and strategies coping with anxiety. A total of 120 students (60 males and 60 females) from Sekolah Menengah Teknik Alor Setar answered Foreign Language Anxiety Classroom Scale developed by Honwitz, Horwitz and Cope (1986) and 8 students (4 males and 4 females) were interviewed. The school-based results were used to represent students' achievement. SPSS 13.0 was employed to analyze the quantitative data and the interviewed data was transcribed and analyzed. The results showed a significant negative correlation between anxiety and achievement but no difference in gender. Participants agreed with the sources of anxiety suggested by Horwitz (1986) namely communication apprehension, fear of negative evaluation, test anxiety and expressed other sources of anxiety such as writing activities and inability to comprehend what is being said. In terms of the manifestation of anxiety, participants showed both physical and psychological signs of anxiety. Some of the symptoms were stutter, palpitation, shaky, tremble, short of breath and restless. Some of the psychological symptoms were to avoid volunteering and demotivated to complete the given tasks. There were five main strategies to cope with anxiety, namely preparation, relaxation, positive thinking, peer seeking and resignation. Based on the findings the author made some pedagogical suggestions in reducing anxiety in language classrooms